Research on Differences of China-American Negotiation Practice Under Cultural Background - Zhao, Ruohan (Transactions on Economics, Business and Management Research, 2024)
The study initiates by examining the cultural disparities existing between China and the United States, recognizing the paramount significance of comprehending cross-cultural negotiation dynamics within the framework of globalization. Three fundamental cultural dimensions are scrutinized: high-context versus low-context communication, individualism versus collectivism, and polychronic versus monochronic time orientations. Leveraging these cultural distinctions, the author furnishes practical recommendations for negotiating strategies. These encompass efficacious approaches for conducting competitive dialogues between the two nations and advocating for interest-based negotiations over positional bargaining. The overarching goal of this research is to align with contemporary trends and integrate insights from experienced negotiators to facilitate smoother business negotiations and diplomatic dialogues between China and the United States. This study contributes to the growing body of literature on cross-cultural negotiation by offering nuanced insights into the cultural nuances that influence negotiation dynamics between China and the United States. By emphasizing the importance of understanding cultural differences, the research provides a framework for negotiators to navigate complex intercultural interactions effectively. Furthermore, the recommendations proposed in the study are grounded in both theoretical frameworks and practical considerations, thereby enhancing their applicability in real-world negotiation scenarios. As globalization continues to shape international business and diplomatic relations, the findings of this study offer valuable guidance for negotiators seeking to bridge cultural divides and achieve mutually beneficial outcomes in negotiations between China and the United States.